Seedling Growth and Mineral Composition of Eucalyptus Hybrid in Light and Heavy Saline and Sodic Soils - Singh, Kalyan (Indian Forester, 2000)
Tolerance of Eucalyptus hybrid to soil salinity and sodicity in light and heavy soils was evaluated under pot culture at varying electrical conductivity (Ece) and exchangeable sodium percentage (ESP) levels on alluvial sandy soil (coarse loamy mixed hyperthermic Typic Ustipsamments) and clayey soils (fine mixed hyperthermic Typic Haplaquept) at addition of different salts. Eucalyptus hybrid failed to grow at Ece 32.8 dSm-1 and ESP at and above 62.3 in heavy soils, and at and above Ece 16.3 dSm-1 and ESP 31.3 in light soils. The successful growth of this species was observed at Ece 16.5 dSm-1 and ESP 30.8 in heavy soils and Ece 8.4 dSm-1 and ESP 15.2 in light soils. Height, girth, fresh and dry weight of plants decreased with increase in ECe or ESP. Although the tolerance of Eucalyptus hybrid to soil salinity and sodicity was more in heavy soils than in light soils. The performance was better at lower levels of ECe and ESP in light soils. Uptake ofNa+ by plants increased progressively with increase in ECe or ESP levels, whereas uptake of Ca++, in general, decreased and Mg++ and K+ were unaffected in both light' and heavy soils. The values of NaIK, Na/Ca and Na/Mg ratios in plants increased with increase in ECe or ESP. Relatively lower uptake of Ca++ due to high concentration of Na+ appeared to increase the adverse effect of sodium on plant growth in light and heavy saline and sodic soils.